2017
DOI: 10.1049/el.2016.2351
|View full text |Cite
|
Sign up to set email alerts
|

2 × VDD output buffer with 36.4% slew rate improvement using leakage current compensation

Abstract: A 2 × VDD output buffer using leakage current compensation is demonstrated. With the proposed leakage current compensation circuit, the SR (slew rate) is improved 36.4-101.89% based on onsilicon measurement results given different VDDIO (1.0/1.2/1.8 V) and temperatures (from 0 to 100°C). The data rate is 510/630/ 400 MHz for VDDIO at 1.8/1.2/1.0 V, respectively. Moreover, the reliability problem, the gate oxide overstress and the hot carrier degradation is avoided. The proposed design is implemented using a ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Several authors have reported on techniques for reducing switch leakage [2][3][4][5], but few on circuit solutions for gate leakage reduction. Several authors [6][7][8] have presented options for minimizing gate leakage but with limited application to high precision track-andhold buffers. Although the industry introduced high-K gate dielectrics to address this gate leakage issue, it remains a limitation at advanced nodes.…”
mentioning
confidence: 99%
“…Several authors have reported on techniques for reducing switch leakage [2][3][4][5], but few on circuit solutions for gate leakage reduction. Several authors [6][7][8] have presented options for minimizing gate leakage but with limited application to high precision track-andhold buffers. Although the industry introduced high-K gate dielectrics to address this gate leakage issue, it remains a limitation at advanced nodes.…”
mentioning
confidence: 99%